Monitoramento da qualidade da água da bacia hidrográfica do ribeirão Maringá - Freire, Rosane (2010)
The aim of this work was monitor the water quality in Maringá stream basin, located at Maringá-PR, in order to make a diagnosis of critical points of water polluting, especially, those derived from discharge of one of the domestic sewage station of treatment and those derived from superficial water flow over farmlands. For this purpose, ten sampling points had been established, located along the basin from its source to its mouth (Pirapó River-PR), with sampling points before and after this confluence. Besides, to obtain hydraulic parameters of this watercourse had been established four fluvial points at Maringá stream. The sampling had been done from September/2008 to December 2009. The water quality had been evaluated in comparison to the standards established in the CONAMA Resolution nº 357/2005. To evaluate the impact caused by domestic sewage discharges in Maringá stream, had been applied the QUAL2E mathematic model, with QUAL2R interface, to determinate its autodepuration capacity The results had pointed out that the characteristics physics, chemicals and biologics obtained in this research to Maringá stream, allowed to reducing its rank to class 3. The critical points of water polluting started with the input of Mandacarú streams, extending until its mouth. The parameters that frequently demonstrated concentrations in disagreement with Brazilian Water Quality Legislation (CONAMA 357/2005) were total ammoniacal nitrogen, nitrites, total phosphorus, dissolved oxygen, biochemical oxygen demand, thermal tolerant coliforms, and the metals: Al, Cd, Pb, Cu, Cr, Mn, Zn. One source of these metals at this basin may be in the use of agrochemicals that, in the rain period, are transported through channel by superficial soil running. About the organic parameters, the mathematic model indicated that, due to effluents characteristics discharged by one of the domestic sewage station of treatment, as well as, the Maringá stream hydraulics characteristics, this watercourse cannot assimilate totally the polluting charge launched. Thus, it's possible to presume that the Maringá stream basin aquatic ecosystems are seriously damaged and the major preoccupation in this moment turns on to Pirapó River.